Hypodermoclysis in Palliative Care - Alen Breček; Romana Bastalić; Andreja Oković; Marta Čivljak (Southeastern European Medical Journal)
With the aging population, the prevalence of oncological and other incurable chronic diseases is increasing, which raises the demand for palliative care. Patients in the final stages of illness often experience reduced food and fluid intake, leading to dehydration, while impaired swallowing hinders the oral administration of medications. Traditionally, fluid replacement is performed via intravenous (IV) routes; however, in elderly patients with long-term comorbidities and compromised veins, establishing venous access can be challenging and traumatic. Subcutaneous infusion, also known as hypodermoclysis, represents a simpler and less invasive alternative, especially in palliative care.